2022
DOI: 10.2174/1389450123666220826160123
|View full text |Cite
|
Sign up to set email alerts
|

Elabela Peptide: An Emerging Target in Therapeutics

Abstract: Elabela, a bioactive micropeptide, is recognized as the second endogenous ligand for Apelin receptor and is widely distributed in different tissues and organs. Elabela plays important role in various physiological processes such blood pressure control, heart morphogenesis, apoptosis, angiogenesis, cell proliferation, migration, etc. Elabela is also implicated in pathological conditions like cardiac dysfunctions, heart failure, hypertension, kidney diseases, cancer and CNS disorders. The association of Elabela … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Elabela is a micropeptide recognized as the second endogenous ligand for APJ [26]. Its involvement in physiological and pathological conditions will not be discussed in this review.…”
Section: Physiology Of the Apelin/apj Systemmentioning
confidence: 99%
“…Elabela is a micropeptide recognized as the second endogenous ligand for APJ [26]. Its involvement in physiological and pathological conditions will not be discussed in this review.…”
Section: Physiology Of the Apelin/apj Systemmentioning
confidence: 99%
“…Recent studies have indicated the importance of apela in various physiological and pathological processes 13 . Apela is a peptide with 55‐amino acid secretory precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Elabela (Ela), a recently discovered peptide hormone (also called Apela/Toddler) is a molecule composed of thirty-two amino acids. It’s an endogenous ligand for apelin (APJ), a G-protein-coupled-receptor[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%